Optimal Priority Structure, Capital Structure, and Investment - Hackbarth, Dirk; Mauer, David C. (Review of Financial Studies, 2012)
[We study the interaction between financing and investment decisions in a dynamic model, where the firm has multiple debt issues and equityholders choose the timing of investment. Jointly optimal capital and priority structures can virtually eliminate investment distortions because debt priority serves as a dynamically optimal contract. Examining the relative efficiency of priority rules observed in practice, we develop several predictions about how firms adjust their priority structure in response to changes in leverage, credit conditions, and firm fundamentals. Notably, financially unconstrained firms with few growth opportunities prefer senior debt, while financially constrained firms, with or without growth opportunities, prefer junior debt. Moreover, lower-rated firms are predicted to spread priority across debt classes. Finally, our analysis has a number of important implications for empirical capital structure research, including the relations between market leverage, book leverage, and credit spreads and Tobin's Q, the influence of firm fundamentals on the agency cost of debt, and the conservative debt policy puzzle.]